Pemikiran Syaikh Abdurrazzaq Bin Abdul Muhsin Al-Badr tentang Peran Orang Tua dalam Mendidik Anak dalam Buku Rakaaiz Fii Tarbiyatil Abna - Sheren Issaura; Asep Dudi Suhardini; Fitroh Hayati (UNISBA Press, 2022)
Abstract. Case the most important things that are prioritized and emphasized by the Prophet Muhammad is Tarbiyah (education). Because of this case is very important, we often meet this case in authentic hadiths. Rasulullah SAW guides and gives instructions on what attitudes, roles and what should be done from an early age as the first bearer of responsibility for education of their children. When someone has blessed by Allah SWT with a child, of course he will hope that his son later become a pious child or shalihah. Because a pious child and shalihah is the one who will do good (filial piety) to his parents later in this world and in the hereafter. In order to achieve the efforts of parents in educating their children, the author is interested in researching